A Rare Case of Guillain-Barré Syndrome With Severe Pandysautonomia - Eneti Tagaloa BS; Frederick Venter MD; Li Liang BS; Jasbir Bhaika MD; David Aguirre MD; Janushe Patel MD; Faisal Nasrawi BS (SAGE Publishing, 2021)
Acute pandysautonomia is a rare disorder characterized by autonomic failure affecting sympathetic, parasympathetic, and enteric functions. We present a case of acute inflammatory demyelinating polyneuropathy (AIDP) with severe pandysautonomia in a young, otherwise healthy, female who presented with gastrointestinal symptoms and sensory demyelinating polyneuropathy, which progressively worsened and subsequently developed bladder dysfunction and orthostatic hypotension. We discuss the challenges with diagnostic workup as well as the challenges we encountered as part of the management.